2017
DOI: 10.4172/2167-0501.1000223
|View full text |Cite
|
Sign up to set email alerts
|

NOS Expression in Oxidative Stress, Neurodegeneration and Male Infertility Induced by the Abuse of Tramadol

Abstract: Tramadol is widely used as a pain reliever; stimulant and it may delay ejaculation. But chronic tramadol users have adverse side effects. Aim:To clarify the worst effect of tramadol hydrochloride on male fertility and its role in neurodegeneration disorders due to oxidative stress in spite of indeed its use as ejaculation delaying. Materials and methods:This experimental study was performed upon 30 adult wistar rats. They were purchased from the National Research Centre Cairo, Egypt. These rats were divided in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Oxidative stress with overexpression of nitric oxide synthase (NOS) are declared as the most important possible pathophysiology for tramadol-induced suppressive impact on spermatogenesis added to spermiological parameters (El-Baky A. and Hafez M., 2017). Oxidative stress conditions have also been shown to initiate progressive aponecrosis, necrosis, and ferroptosis in male testicular tissue, resulting in male fertility loss (Alahmar 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress with overexpression of nitric oxide synthase (NOS) are declared as the most important possible pathophysiology for tramadol-induced suppressive impact on spermatogenesis added to spermiological parameters (El-Baky A. and Hafez M., 2017). Oxidative stress conditions have also been shown to initiate progressive aponecrosis, necrosis, and ferroptosis in male testicular tissue, resulting in male fertility loss (Alahmar 2019).…”
Section: Discussionmentioning
confidence: 99%
“…TAM was impressively capable of implementing its malignant activities in the production of the testis as well as the function and, thus, the regulation of serum hormonal levels that regulate the male richness [27,36,37]. Furthermore, Abdel-Hamid et al [7] suggested that TAM may exhibit a beneficial effect on premature ejaculation therapy. Rats treated with E. brevicornum at a dose of 2.43 g/kg/day for 130 consecutive days elicited a remarkable increase in sperm motility and count, with a marked decrease in sperm abnormalities compared to the control or TAM-treated groups.…”
Section: Discussionmentioning
confidence: 99%
“…TAM has been reported to cause respiratory depression and psychological and physiological addiction [5]. Moreover, long-term administration of TAM results in an increase in oxidative stress that causes male infertility due to low levels of testosterone and neurodegenerative diseases such as Alzheimer's disease [6,7]. There is a disturbing increase in the abuse of TAM, mainly among young people assuming that it improves sexual excitement and climax without the development of sexual dysfunctions [8], and small quantities for additional investigations and examinations have been implanted [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is marked in the body of boars by a decrease in the activity of SOD and CAT (Shostya et al, 2020). The decrease in CAT activity occurs due to the high sensitivity to NO, the content of which increases significantly under the influence of OS (El-Baky & Hafez, 2017). It is known that SOD provides catalase with a substrate -hydrogen peroxide, however the activity of both enzymes was significantly reduced.…”
Section: Discussionmentioning
confidence: 99%